Liquid chromatography coupled to tandem mass spectrometry for comprehensive quantification of crustacean tropomyosin and arginine kinase in food matrix. (October 2022) - Li, Huan; Li, Tianshu; Wang, Yanbo; Zhang, Shuifeng; Sheng, Huadong; Fu, Linglin
Abstract: Crustacean has been recognized as one of the most critical food allergens whose impact could develop or persist into adulthood. It's urgently needed to establish accurate and reliable methods to quantify tropomyosin (TM) and arginine kinase (AK), the primary allergenic proteins in crustaceans. Herein, we developed an ultra-high performance liquid chromatography coupled to tandem mass spectrometry (UHPLC-MS/MS) method based on stable isotope-labeled internal standard (SIIS) to quantify TM and AK simultaneously. The amino acid sequences of TM and AK from the mostly consumed crustaceans in the world were analyzed, and the signature peptides of the two allergenic proteins were selected given the specificity, stability, and mass spectrometry responsiveness. Under the optimal detection conditions, signature peptide FLAEEADR and VSSTLSSLEGELK were able to quantify TM and AK in a complex food matrix with high accuracy (recoveries: 94.11%–102.16%) and precision (intra- and inter-day RSD<10%). At the same time, a signature peptide of TM, ALSNAEGEVAALNR, was found to be absent in crab. The proposed method exhibited a broad linear range (0–1000 ng/mL) of the absolute quantification (AQUA) peptides with R 2  > 0.99 and took approximately 11 h per analysis. Moreover, it was successfully applied for quantifying TM and AK in commercial food samples, indicating the great applicable potential. The proposed method can reveal the allergenic risk of crustacean-related food and thus help allergic individuals avoid such food intake. Highlights: Signature quantification peptides were selected for primary crustacean allergens. A SIIS-based UHPLC-MS/MS method for absolute quantification of crustacean allergens. Promising detection performance in complex food matrix was observed.